Constraints on the Neogene growth of the central Patagonian Andes at the latitude of the Chile triple junction (45–47°S) using U/Pb geochronology in synorogenic strata - Folguera Telichevsky, Andres; Encinas, Alfonso; Echaurren Gonzalez, Andres; Gianni, Guido Martin; Orts, Darío Leandro; Valencia, Víctor; Carrasco, Gabriel (Tectonophysics)
Desertification of Central Patagonia began between ~14–12 Ma and therefore was not directly connected to the opening of the Drake Passage and initial conformation of the Antarctica ice cap in early Miocene times. Local processes, in particular the uplift of the Southern Andes, seem to have played a major role in climatic and biotic changes. We studied synorogenic strata filling a partly cannibalized foredeep between ~45° and 47°S at the latitudes of the Chile triple juction. Older synorogenic successions have yielded 18.7–16.4 Ma (U-Pb) in the western sector of the North Patagonian Cordillera corresponding to Meseta Guadal, Jeinemeni and Alto de Río Cisnes sections. This uplift was partly contemporaneous with broken foreland deformation associated with the San Bernardo fold belt to the east at 17.7–15 Ma. Younger synorogenic successions of 13.5 Ma (U-Pb), associated with a short pulse of major uplift that gave way to deposition of a thick conglomeratic succession, and subsequently finer-grained deposits of 12.3 Ma, are on the eastern Andean front in the Chalía and Guenguell sections, implying a retraction in orogenic activity, and out-of-sequence growth of the Patagonian Cordillera. Consequently, contractional deformation in this area ended after ~12 Ma, sealed by the extrusion of extensive alkali flood basalts, indicating that Neogene shortening only lasted ~6 My, ending around 6 My before the subduction of the Chile Ridge at the latitudes of Central Patagonia and 4.5 My before subduction at the southern tip of South America. Fil: Folguera Telichevsky, Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Encinas, Alfonso. Universidad de Concepción; Chile Fil: Echaurren Gonzalez, Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. ...